ANALYSIS OF PRODUCTION PLANNING FUNCTIONS IN SEWING ENTERPRISES IN "1C:CRM" SOFTWARE SYSTEM - D.Kabilova; G.G. Bazarbaeva; Xasanov.Z, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article analyzes production planning processes at sewing enterprises in the 1C:CRM software system. During planning, the main functions of the program, the main technological operations in the program, maps and the procedure for placing a production order in the software package were formed.